2008
DOI: 10.1016/j.theriogenology.2007.11.019
|View full text |Cite
|
Sign up to set email alerts
|

Repeatability of preovulatory follicular diameter and uterine edema pattern in two consecutive cycles in the mare and how they are influenced by ovulation inductors

Abstract: Follicular diameter is used as a guiding tool to predict ovulation in the mare. However, the great range in preovulatory follicular diameter makes prediction of optimal breeding time based on follicular diameter unreliable. Uterine edema pattern is also useful to determine the best time to breed, since intensity of edema tends to dissipate as ovulation approaches, however, not every mare follows this pattern. The aims of this study were to assess the repeatability of preovulatory follicular diameter and uterin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 12 publications
1
21
0
3
Order By: Relevance
“…The diameter of dominant follicles and uterine edema findings are considered effective indicators to predict ovulation timing in horses [3, 21, 28, 32]. The mean maximum diameter of the ovulatory follicle is usually between 40 and 45 mm, but there are variations depending on season and type of horse [32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diameter of dominant follicles and uterine edema findings are considered effective indicators to predict ovulation timing in horses [3, 21, 28, 32]. The mean maximum diameter of the ovulatory follicle is usually between 40 and 45 mm, but there are variations depending on season and type of horse [32].…”
Section: Discussionmentioning
confidence: 99%
“…Uterine edema findings become most clear approximately 3 days before ovulation, but decrease 1 to 2 days before ovulation, thus uterine edema is considered an effective indicator for the timing of ovulation [3, 11]. However, uterine edema findings were found in 64% of anovulatory cycles during the breeding transition period [36], and significant uterine edema findings are also observed in endometritis [31].…”
Section: Discussionmentioning
confidence: 99%
“…Mares with short intervals are usually found with a large follicle (>30 mm) at the time of flushing (time of PGF treatment), whereas mares with long IOI have small follicles at the time of flushing which may take 10-16 days to grow and ovulate or on fewer cases may have a large follicle which does not ovulate but regresses. It has been shown that there is a good degree of individual repeatability in the preovulatory follicular diameter (Cuervo-Arango and Newcombe, 2008) and in the length of the IOI within consecutive cycles of individual mares (reviewed by Ginther, 1992). …”
Section: Discussionmentioning
confidence: 99%
“…Christoffersen et al [31] showed that mares susceptible to endometritis had a prolonged endometrial gene expression of proinflammatory cytokines compared with resistant mares in response to experimentally induced endometritis. It can be difficult to compare edema patterns between mares because of differences in estrogen profiles; however Cuervo-Arango and Newcombe [39] investigated the repeatability of the endometrial edema pattern in two consecutive cycles in mares. They found a fair correlation (Spearman rank correlation, r ¼ 0.71) of the endometrial edema pattern between the cycles.…”
Section: Discussionmentioning
confidence: 99%